JavaScript Object Notation (JSON) - Zaidi, Rehan (JavaScript Essentials for SAP ABAP Developers, 2017)
This chapter introduces the various ways you can use JavaScript Object Notation. It starts with an overview of JSON and then dives into the details of the data types used in JSON. You will then see how the JSON arrays and objects work in JS programs. Finally, you will see two useful methods, parse and stringify, of the JSON object.